2012
DOI: 10.2174/156720512799361664
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Anti-Amyloidogenic Secretase ADAM10 in Shedding the APP-like Proteins

Abstract: ADAM10 (A disintegrin and metalloproteinase 10) has been demonstrated as an enzyme with protective properties in Alzheimer's disease: in mouse models it not only lowered generation of toxic A-beta peptides and formation of senile plaques but also alleviated learning deficits and enhanced synaptic density. This is due to cleavage of the amyloid precursor protein (APP) within its A-beta stretch and to the release of the extracellular domain of APP with neuroprotective function. Aside from cleaving APP, ADAM10 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 97 publications
0
23
0
Order By: Relevance
“…It is well established that APP and APLPs can form homo-and heterodimers, arguing for a functional connection between these molecules (Soba et al 2005;Kaden et al 2011). APLP1 and APLP2 do not contain an Ab-domain, but their ectodomains are shedded in an ADAM10-dependent manner similar to that observed for APP (Jacobsen and Iverfeldt 2009;Endres and Fahrenholz 2011;Hogl et al 2011;Kaden et al 2011). In line with this hypothesis, neuroprotective IGF-1 signalling induces anti-amyloidogenic processing of APP and ectodomain shedding of APLP1 and APLP2 in human SH-SY5Y neuroblastoma cells (Adlerz et al 2007).…”
Section: App Family Members and Neuroprotectionmentioning
confidence: 88%
“…It is well established that APP and APLPs can form homo-and heterodimers, arguing for a functional connection between these molecules (Soba et al 2005;Kaden et al 2011). APLP1 and APLP2 do not contain an Ab-domain, but their ectodomains are shedded in an ADAM10-dependent manner similar to that observed for APP (Jacobsen and Iverfeldt 2009;Endres and Fahrenholz 2011;Hogl et al 2011;Kaden et al 2011). In line with this hypothesis, neuroprotective IGF-1 signalling induces anti-amyloidogenic processing of APP and ectodomain shedding of APLP1 and APLP2 in human SH-SY5Y neuroblastoma cells (Adlerz et al 2007).…”
Section: App Family Members and Neuroprotectionmentioning
confidence: 88%
“…The disintegrin metalloproteases, ADAM-10 (a disintegrin and metalloproteinase domain-containing protein 10), ADAM-17/tumor necrosis factor α-convertase (TACE), and ADAM-9, that have a consensus zinc binding motif, HEXXH, in their catalytic domain [29], fulfill some of the criteria required of α-secretases [6]. ADAM-10 interacts with synapse-associated protein-97 (SAP97) to prevent amyloidogenesis [3032], decreases generation of toxic Aβ peptides, reduces senile plaques and alleviates learning deficits [33] in human APP transgenic mice (ADAM10 × APP[V717I]) [34]. …”
Section: Iron and Inflammation In Ad And Translational Control Of mentioning
confidence: 99%
“…The results showed that the levels of these two proteins were significantly lower in the Cd treatment group. ADAM10 has a protective role in AD (20). Therefore, we speculated that Cd inhibits the activity of α-secretase, which leads to a greater metabolism of APP through the β-secretase pathway and an increase in Aβ.…”
Section: A B Cmentioning
confidence: 99%